Morpho-physiological traits contributing to better yield performance of japonica/indica hybrids over indica hybrids under input-reduced practices - Huan-he WEI; Tian-yao MENG; Jia-lin GE; Xu-bin ZHANG; Yu LU; Xin-yue LI; Yuan TAO; En-hao DING; Ying-long CHEN; Qi-gen DAI (Journal of Integrative Agriculture, 2020)
It is widely reported that japonica/indica hybrids (JIH) have superior grain yield over other main varietal groups such as indica hybrids (IH) under sufficient resource inputs. To date, little attention has been paid to yield performance of JIH under input-reduced practices, and whether JIH could have better grain yield performance over IH under input-reduced practices. In this study, three JIH varieties and three IH varieties were compared in grain yield and their related morpho-physiological traits under two cultivation modes, i.e., conventional high-yielding method (CHYM) and double reductions in nitrogen rate and planting density (DRNP). Our results showed that JIH had 8.3 and 13.3% higher grain yield over IH under CHYM and DRNP, respectively. The superior grain yield of JIH over IH under DRNP was mainly attributed to larger sink size and improved sink filling efficiency. Three main morpho-physiological traits were concluded for better yield performance of JIH over IH under DRNP. Firstly, JIH had the reduced unproductive tillers growth, indicated by a higher percentage of productive tillers and the percentage of effective leaf area index (LAI) to total LAI at heading stage. Secondly, a synergistic increase in biomass accumulation and harvest index were achieved of JIH, supported by higher biomass accumulation and leaf area duration during the main growth periods, and improved non-structural carbohydrate (NSC) remobilization after heading. Thirdly, JIH had an improved canopy structure, showing as higher leaf area of upper three leaves and lower light extinction coefficient. Our results suggested that improved morpho-physiological traits of JIH could lead to better grain yield performance over IH under input-reduced practices.